Proposal for Creating an Electronic Journal on Computer Architecture Education - Anselmo, Dayse N.; Mendes, Israel T.; Silveira, Luiz Guilherme H. D.; Carvalho, Milene B.; Campos Jr, Roberto de O.; Martins, Carlos Augusto P. S. (International Journal of Computer Architecture Education, 2012)
Worldwide, there are events organized to meet the need for information exchange among people involved in computer architecture education. At these usually annual meetings, there are presentations of works related to education, and opportunities are created for discussions and exchanges of experiences among participants. An alternative for publishing works is continuous-flow journals, where works made available digitally are accessed by various people. Although these are important means of disseminating information, none of them alone is ideal for reaching a large audience and allowing people to present and discuss ideas. Therefore, this article presents a hypothesis that aims to complement these means of dissemination and information exchange: the creation of an electronic journal on computer architecture education. In this journal, it would be possible to combine presentations and discussions present at events with the broader reach presentations of continuous-flow journals.